Transtracheal ultrasonography versus endtidal capnography in rapid confirmation of endotracheal tube placement - Shruthi Rioniz,; Nischala Dixit,; Preethi Rioniz,; Thomas T Vellapally,; Nayanthara Joachim,; Siddhanth Suresh, (Asian Journal of Medical Sciences, 2025)
Background: Prompt confirmation of proper endotracheal (ET) tube placement after intubation is imperative to averting life-threatening consequences. Waveform capnography, although the gold standard method, poses some limitations while transtracheal ultrasonography (USG) is a reliable real-time technique that has shown much promise. Existing literature on the faster method has yielded conflicting results.Aims and Objectives: This study aims to determine the mean time taken to confirm the correct placement of the ET tube using both transtracheal USG and end-tidal capnography. A comparative assessment of the faster method will supplement patient care by helping anesthesiologists avoid accidental esophageal/endobronchial intubation and the associated morbidity.Materials and Methods: Consenting adult patients posted for elective surgeries under general anesthesia were recruited over a period of 18 months. The time taken for confirmation of correct tube placement by both transtracheal USG and capnographic end-tidal carbon dioxide tracing was recorded. A paired samples t-test was used to compare the means (±standard deviation).Results: The study included 112 patients aged 40.1±12 years of whom 59 (52.6%) were females. The mean time taken to confirm tube placement by USG and capnography was 35.8±9.8 s and 67.4±13.7 s, respectively, with a mean time difference of 31.6±7.8 s which was found to be statistically significant (P